Alumni’s Perceptions about Commitment towards their University: Drivers and Consequences - Pedro, Ilda Maria; Mendes, Júlio da Costa; Pereira, Luís Nobre; Sequeira, Bernardete Santos (ICAReAlumni Conference Proceedings, 2019)
Purpose: This paper intends to capture alumni’s assessments and perceptions about decisive dimensions of their commitment towards their alma mater. Their academic experience and current situation are highlighted. Moreover, their perception about the role of Higher Education Institution (HEI) in this commitment-relationship is likewise valuable to get their involvement. Design: The study took place at a Portuguese university. Three focus groups, with 21 participants, were conducted to get consistent information permitting further developments. Data were analysed through NVivo software. Findings: The study gives interesting insights revealing dimensions such as the relationships with teachers, extra-curricular activities and initiation as decisive in their academic experience (AE). Recommending and sharing their experience, underline evidence of what they are willing to give back. A strong sense of belonging defined alumni statements, as well as pride at being part of the university. But they all demand an effective ability of the university to communicate with them. Value: Overall conclusions offer a clear scenario of alumni’s commitment, giving HEI’s management valuable clues to improvement, but its responsibility in this commitment-relationship was also stressed. Moreover, results also provide strong contributions to literature enabling other HEIs to replicate the study or simply use the results for their own development.